Preface (TEST Antologia di Diritto Pubblico, 2026)
This contribution, in accordance with the Regulations of Antologia di Diritto Pubblico, inaugurates the biennial publication of special issues entitled “Classici in collana”. It serves as an introduction to the issue devoted to the interpretation of administrative acts, based on selected excerpts from the monograph by Massimo Severo Giannini, L’interpretazione dell’atto amministrativo e la teoria giuridica generale dell’interpretazione (Milan, Giuffrè, 1939).
Keywords: Massimo Severo Giannini; interpretation; administrative act